Necrotic Enterocolitis: Clinical and Anamnestic Parallels in Premature Infants. - Olena Vasylivna Vlasova; Mariana Ivanivna Hrytsiuk; Larisa Viktorovna Kolyubakina; Natalia Vasylivna Homma (Kazimierz Wielki University, 2020)
Necrotic enterocolitis (NEC) in neonatal practice remains one of the major causes of morbidity and mortality in premature infants due to the combined effect of various pathogenic factors: infectious, metabolic, circulatory on the relatively immature bowel. Most often the onset of the disease occurs at the gestational age of the baby 29-32 weeks at the age of 2-3 weeks of life. Objective of study: evaluation of anamnestic, clinical and paraclinical data and course of NEC in premature infants who were hospitalized in the neonatal unit of Regional Children's Clinical Hospital (RCCH) of Chernivtsi. Materials and methods. A retrospective analysis of the diseases of 28 premature infants who were hospitalized in the neonatal intensive care unit (NICU) of RCCH was performed. While in the hospital, all children underwent general clinical, biochemical, instrumental methods of investigation and determination of immunological parameters of the infectious-inflammatory process in the blood serum, namely the level of C-reactive protein and pressepsin was made. Results. Among the examined, the proportion of deeply premature infants (up to 32 weeks of gestation) was 50%, including extremely low weight 17.8%. About 80% of children were born with signs of asphyxia of varying severity. It was shown that the development of NEC in premature children is associated with a burdened infectious history in mothers amid anemia (r = + 0.79), a short gestation period (r = + 0.44), and a low Apgar score in the fifth minute (r = + 0.45), the severity of the condition at  admission to the hospital (r = + 0.74), the need for long-term mechanical ventilation (r = + 0.67), hemodynamic support with the vasoactive drugs (r = + 0.39), apnea development (r = + 0.83), feeding intolerance (r = + 0.45) and thrombocytopenia (r = +0.68). It was established that the determination of serum presepsin content makes it possible to verify the genesis of the development of NEC. Conclusion. The formation of NEC in premature infants is associated with the development of multiple organ failure in the anamnesis due to asphyxia, and its chances are increased due to the presence of a generalized infectious inflammatory process.